Sex Differences in Platelet Toll-Like Receptors and Their Association With Cardiovascular Risk Factors. Issue 4 (April 2015) - Koupenova, Milka; Mick, Eric; Mikhalev, Ekaterina; Benjamin, Emelia J.; Tanriverdi, Kahraman; Freedman, Jane E.
<x xml:space="preserve">Abstract</x> Objective— Platelets contribute to thrombosis, and platelet toll-like receptors (TLRs) are central in pathogen detection, potentially mediating infection-induced vascular occlusion. Using a large community-based cohort study, we sought to examine if platelets express all known TLR transcripts and analyze their association with cardiovascular risk factors. Approach and Results— mRNA levels for TLRs were measured in isolated platelets by high-throughput quantitative reverse transcriptase polymerase chain reaction in 1625 participants (mean age, 66.6±9; 54% women) of the Framingham Heart Study. We measured circulating inflammatory and thrombotic markers (C-reactive protein, interleukin-6, monocyte chemoattractant protein 1, intracellular cell adhesion molecule 1, soluble tumor necrosis factor-α receptor 1, and soluble p-selectin) and analyzed TLRs and their association with sex and cardiovascular risk factors by multivariable logit regression model adjusted for confounding factors. Platelets expressed all 10 TLR transcripts, and all TLRs were coexpressed. Women had higher platelet TLR expression, which associated with different cardiovascular risk factors, compared with men. In women, TLR1, TLR3, TLR6, and TLR7 were associated with body mass index and TLR5, TLR7, and TLR10 were associated with total cholesterol to high-density lipoprotein ratio. In men, TLR1, TLR2, and TLR3 were associated with lipid and TLR8 with hypertension treatment. Similarly, TLR expression in men was more commonly associated with circulating inflammatory markers (soluble tumor necrosis factor-α receptor 1 and intracellular cell adhesion molecule 1), whereas in women, TLR expression was associated with soluble p-selectin levels. Conclusions— We report the first study to demonstrate that platelets express all TLR transcripts using a large community-based observational cohort. These transcripts are more abundant in women and have distinct associations with cardiovascular risk and inflammatory biomarkers that vary by sex.